Health tips in newspapers: a matter of concern - Pushparaja Shetty (The Pan African Medical Journal, 2020)

(untitled)
Newspapers are a significant source of information to the general public as it reaches quite large numbers. Many readers make an essential health decision based on the information provided by the newspaper. Evidence suggests that that quality of health reporting in the newspaper is poor. Most of the health tips in the newspaper may lead to self-medication, which is most dangerous. It is the responsibility of the newspaper to provide health information with scientific evidence and readers to be cautious before making any health-related decision based on newspaper information without consulting experts.